2016
DOI: 10.7150/ijbs.15071
|View full text |Cite
|
Sign up to set email alerts
|

BDNF-mediates Down-regulation of MicroRNA-195 Inhibits Ischemic Cardiac Apoptosis in Rats

Abstract: Background: Our previous studies suggested that brain-derived neurotrophic factor (BDNF)/tropomyosin-related kinase B (TrkB) axis inhibited cardiomyocyte apoptosis in myocardial infarction (MI). However, the relationship between BDNF and microRNA (miRNA) in cardiomyocytes are unclear. The present study was performed to investigate the role of miR-195 and the interplay between BDNF and miR-195 in ischemic cardiomyocyte apoptosis.Methods: Male Wistar rats were subjected to coronary artery ligation, and primary n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 37 publications
4
34
1
Order By: Relevance
“…Given that apoptosis and the subsequent cell loss, which were stimulated by oxidative stress, have been considered a driving force and the major mechanism in sepsis-induced myocardial dysfunction [37], the observed cardioprotective effects of BDNF in the hearts from septic shock rats may act through reducing oxidative stress and the subsequent reduction of cardiomyocytes apoptosis. Our findings were similar to the study by Hang et al which showed that BDNF by downregulating microRNA-195 inhibited cardiac apoptosis and attenuated myocardial ischemia reperfusion injury in rats [38]. In the current study, we further demonstrated that the abovementioned beneficial effects of BDNF were mainly through NOS system.…”
Section: Discussionsupporting
confidence: 92%
“…Given that apoptosis and the subsequent cell loss, which were stimulated by oxidative stress, have been considered a driving force and the major mechanism in sepsis-induced myocardial dysfunction [37], the observed cardioprotective effects of BDNF in the hearts from septic shock rats may act through reducing oxidative stress and the subsequent reduction of cardiomyocytes apoptosis. Our findings were similar to the study by Hang et al which showed that BDNF by downregulating microRNA-195 inhibited cardiac apoptosis and attenuated myocardial ischemia reperfusion injury in rats [38]. In the current study, we further demonstrated that the abovementioned beneficial effects of BDNF were mainly through NOS system.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies indicate that BDNF plays an important role in the regulation of hippocampal synaptic plasticity [24]. BDNF has also been reported to be an important regulator of neuronal apoptosis [25,26]. In the present study, we found that after diabetic modeling, BDNF expression was decreased, while resveratrol treatment reversed the down-regulation.…”
Section: Discussionsupporting
confidence: 66%
“…Other nuclear-encoded miRNAs have been found to directly regulate mitochondrial proteins in the ischemic heart. For example, the upregulation of miR-15/16 family and miR-195 suppressed ATP levels and induced mitochondrial fusion, by acting on their common target ADP-ribosylation factor-like 2 to influence cardiomyocyte survival and contribute to myocardial infarction [61][62][63]. Inhibition of miR-15 family protected against ischemia/reperfusion heart injury in vivo through directly de-repression of pyruvate dehydrogenase kinase 4 and serum/glucocorticoid-regulated kinase 1, which regulate mitochondrial function and apoptosis, respectively [61].…”
Section: Ischemic Heart Diseasementioning
confidence: 99%